1996
DOI: 10.1007/bf03349012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on insulin receptor mRNA levels, RNA stability and isotype RNA pattern in U-937 human promonocytic cells

Abstract: The administration of 5 x 10(-6) mol/l dexamethasone transiently increased insulin receptor (IR) mRNA levels in U-937 human promonocytic cells, which reached the maximum level at 15 h of treatment. Dexamethasone treatment did not affect the IR mRNA half-life (approximately 4 h), suggesting that the increase is regulated at the transcriptional level. The stimulatory action of dexamethasone was not prevented by the simultaneous presence of the protein synthesis inhibitor cycloheximide, indicating that the induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, there are five glucocorticoid-like response elements (GREs) [21,24] These GREs were well characterized by Lee et al [21,24] through transfection experiments and footprinting assays. We studied the possibility that these GREs could account for the increased hIR mRNA levels associated with the transcriptional induction of this gene by glucocorticoids [25][26][27], and with the transcriptional inhibition of this gene by mineralocorticoids [27][28][29], using U-937 cells. Our results indicated that dexamethasone action mediated by the glucocorticoid receptor GR, specifically recognized four of the five GREs: dGRE, cGRE2, cGRE3 and pGRE, while the action of aldosterone mediated by the mineralocorticoid receptor MR, specifically recognized three: cGRE1, cGRE3 and pGRE.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are five glucocorticoid-like response elements (GREs) [21,24] These GREs were well characterized by Lee et al [21,24] through transfection experiments and footprinting assays. We studied the possibility that these GREs could account for the increased hIR mRNA levels associated with the transcriptional induction of this gene by glucocorticoids [25][26][27], and with the transcriptional inhibition of this gene by mineralocorticoids [27][28][29], using U-937 cells. Our results indicated that dexamethasone action mediated by the glucocorticoid receptor GR, specifically recognized four of the five GREs: dGRE, cGRE2, cGRE3 and pGRE, while the action of aldosterone mediated by the mineralocorticoid receptor MR, specifically recognized three: cGRE1, cGRE3 and pGRE.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory is involved in the study of the regulation of insulin receptor (IR) gene expression by different steroid hormones, such as glucocorticoids [12,13], mineralcorticoids [14] and 1,25(OH)2D3 [15]. The IR gene codifies the protein (IR) responsible for transducing the insulin signal into the target cells [16,17], thus initiating the wide spectrum of cellular insulin effects.…”
mentioning
confidence: 99%
“…The IR kinase activation serves for both autophosphorylation and phosphorylation of multiple cellular substrates [18], i.e. the IR substrate protein family [12,22], and provide a useful in vitro model to study IR gene expression and its modulation by diverse hormones [12][13][14][15]24]. With these antecedents, the aim of the present work was to examine whether the stimulation of IR gene expression by 1,25(OH)2D3 might be dose-dependent and whether it could involve regulation of both insulin binding and insulin action in terms of glucose transport in U-937 cells.…”
mentioning
confidence: 99%
“…In addition, it is known that the mature IR exists as two isoforms, namely A (lacking exon 11) and B (containing exon 11) which arise from alternative splicing of the primary transcript (8,9). It has been reported that the synthetic glucocorticoid, dexamethasone, regulates the splicing of IR mRNA in certain cell lines (10,11), but not in all (4,10), while 1,25-dihydroxyvitamin D3 has no modulation effect at all on IR mRNA splicing (7).…”
Section: Introductionmentioning
confidence: 99%